First Year Prospective Teachers’ Perceptions of Chemical Solution Types and Solubility - ÇOKADAR, HULUSI (Asian Journal of Chemistry, 2009)
This study aims to compare first-year prospective elementary science and primary teachers' perceptions of chemical solution types and solubility. A questionnaire was administered to 89 prospective elementary science and 86 prospective primary teachers in the Faculty of Education at Pamukkale University in Turkey, during 2007-2008 schooling year. The questionnaire is consisted of three two-tiered questions and one solubi-lity problem. Question-1 examines participants' perceptions about types of the solutions. Questions-2 and 3 examine the participants' perceptions about the concentration of a saturated solution when a small amount of solute is added into the solution and when half of water evaporates from the solution, respectively. Questions 1 to 3 also asked participants to write the reasons for their answers. Question-4 explores the participants' skills to solve a solubility problem. Responses were analyzed by quantitative and qualitative methods. The findings showed that prospective teachers have some difficulties to understand solution types and solubility concept.